Effectiveness of Transformational Leadership Education on the Knowledge Level and Work Motivation of Posyandu Cadres in Assisting Health Services in the Puskesmas Working Area: Yulianti Rahayu, Burhanudin Basri, Hadi Abdillah, Ernawati Hamidah - Yulianti Rahayu; Burhanuddin Basri; Hadi Abdillah; Ernawati Hamidah (PROFESSIONAL HEALTH JOURNAL, 2025)
The work motivation of cadres, the role, the attitude of transformational leadership of cadres is needed in encouraging and inviting the community will affect productive age community visits, but the lack of knowledge about leadership and cadre work motivation causes community enthusiasm in Posyandu activities to decrease. The purpose of this study was to determine the level of knowledge of transformational leadership of Posyandu cadres in the Sagaranten Puskesmas work area, to determine the work motivation of Posyandu cadres in the Sagaranten Puskesmas work area, and to analyze the effectiveness before and after transformational leadership education on the level of knowledge and work motivation of Posyandu cadres in assisting health services in the Sagaranten Puskesmas work area. The population in this study were Posyandu cadres with a total of 35 cadres. The sampling technique used was total sampling. In this study the sample was the entire cadre of Posyandu Hegaramanah Village. The research was conducted in Hegarmanah Village, Sagaranten Health Center working area. The research instrument used to collect data is a questionnaire. The results showed that based on the results of statistical tests with the Paired Samples Test, the resulting P value was 0.000 <0.05, where it can be concluded that H0¹ is rejected and Ha¹ is accepted that there is an effectiveness of transformational leadership education on the level of knowledge and motivation level of Posyandu cadres. Based on the results of statistical tests with the Paired Samples Test, the resulting P value was 0.000 <0.05, where it can be concluded that H0² rejected dan Ha² is accepted that there is an effectiveness of transformational leadership education on the level of motivation level of Posyandu cadres.